Higher thinking and digital literacy: Empowering technology for pre-service mathematics teacher - Yanuarto, Wanda Nugroho; Jaelani, Anton (Al-Jabar: Jurnal Pendidikan Matematika, 2021)
Teachers play a more significant role as a symbol of teaching success. Teachers who hold a more potential digital literacy in education teach mathematics with patterns and procedures, leading to practical teaching mathematics. Influential digital literacy and higher thinking are not possible when teachers do not use technology to understand the concept of mathematics. Therefore, teachers are required to improve their technical abilities and higher thinking in mathematics learning. This research used a cross-sectional quantitative research. This research uses statistical analysis of the Kaiser Meyer-Oikin Test (KMO) and the Barlett's Test to obtain exploratory factor analysis. Subsequently, the analyzed using confirmatory factor analysis and structural equation model with Analysis of Moment Structure (AMOS). The purpose of this research is to provide an overview of the relationship between higher thinking skills and digital literacy. The review discoveries show that teachers' digital literacy has a more significant impact on the use of technology in the classroom, and teachers' higher thinking in the role of technology will encourage teachers to use more technology in their practical teaching. Teachers need to broaden their perspectives on the ability and quality of mathematics teaching that is more easily changed by changing practical instruction in the classroom. One of the reasons mathematics teachers still apply traditional teachings is the lower thinking and low level of digital literacy. Teachers are not capable of teaching the concept of mathematics with technology to students.